Investigating Errors in the Usage of Punctuation Marks in the Written English Of Higher National Diploma (HND) Students: A Case Study of the Bolgatanga Polytechnic - Avomah, O.M.A. (University of Ghana, 2005)
The study takes a look a errors in the use of punctuation marks by Higher National Diploma(HND) students with particular reference to students of the Bolgatanga Polytechnic in the Upper East Region. The study which has been organized into five chapters seeks to find out whether students can identify areas in an unpunctuated passage and to insert punctuation marks correctly. Again, the study seeks to find out how students use punctuation marks in their own extended writing. To achieve this objective, an unpunctuated passage was given to students to insert the right punctuations in their appropriate places. An essay topic was given to students to write paying attention to the correct use of punctuation marks. The findings disclosed that generally, students at all levels of education, particularly those of the polytechnics, do not have explicit knowledge in the use of punctuation marks in their writing. the way forward has been suggested in the concluding chapter and relates to practical involvement of syllabus designers, communication skills lecturers, English language teachers, policy makers and other stakeholders. It is the hope of the researcher that if these suggestions are heeded, standards in the polytechnics will improve
MA. Linguistics
Keywords: Higher National Diploma(HND); Bolgatanga Polytechnic; Syllabus; Punctuation Marks